Studi Empiris Penentu Kepuasan Destinasi Wisata Kota Padang Provinsi Sumatera Barat - Abdilla, Mohammad; Idwar, Idwar; Permatasari, Intan; Rajunas, Rajunas (Universitas Dharma Andalas, 2024)
The phenomenon of destination satisfaction is currently drawing attention from the tourism industry in tourist decision-making processes, thus necessitating empirical studies. The aim of this research is to determine the partial and simultaneous effects of trip experiences (X2), trip value (X2), destination personality (X3), perceived risk (X4), and novelty seeking (X5) on destination satisfaction (Y) in the tourism destination of Padang City. With 138 respondents, the research results indicate that, partially, Trip Experiences, Trip Value, Destination Personality, Perceived Risk, and Novelty Seeking significantly and positively influence the destination satisfaction of visitors to tourist attractions in Padang City. The multiple linear regression equation results show that the perceived risk experienced by visitors to tourist attractions in Padang City has a greater influence on destination satisfaction than trip experiences, trip value, destination personality, and novelty seeking. The relationship between the independent variables and the dependent variable is strong (R = 0.875), and the destination satisfaction of visitors to tourist attractions in Padang City is explained by Trip Experiences, Trip Value, Destination Personality, Perceived Risk, and Novelty Seeking by 0.757, while the remaining 0.243 is explained by other factors not included in the research model. Abstrak Fenomena destination satisfaction cukup menarik perhatian industri pariwisata saat ini dalam proses pengambilan keputusan wisatawan sehingga perlu dilakukan studi empiris.Tujuan penelitian ini adalah untuk mengetahui pengaruh trip experiences (X2), trip value (X2), destination personality (X3), perceived risk (X4) dan novelty seeking (X5) terhadap destination satisfaction (Y) pada destinasi pariwisata kota Padang scara parsial dan simultan. Dengan menggunakan 138 responden, Hasil penelitian menunjukan bahwa secara parsial Trip Experiences, Trip Value, Destination personality, Perceived Risk, Novelty Seeking berpengaruh positif signifikan terhadap destination satisfaction pengunjung objek wisata kota Padang. Dari hasil persamaan regresi linier berganda menunjukkan kontribusi perceived risk yang dirasakan pengunjung objek wisata di kota Padang lebih besar pengaruhnya terhadap destination satisfaction daripada trip experiences, trip value, destination personality, dan novelty seeking yang dirasakan pengunjung. Hubungan variabel independen ke variabel dependent hubungannya kuat (R = 0,875) dan destination satisfaction pengunjung objek wisata kota Padang dijelaskan oleh Trip Experiences, Trip Value, Destination personality, Perceived Risk, dan Novelty Seeking sebesar 0,757 sisanya 0,243 dijelaskan oleh faktor lain yang tidak termasuk dalam model penelitian.